Serial Cases Report : 3 Cases Of Giant Bladder Stone In Dilumilpublic Health Center, East Nusa Tenggara, Indonesia - Wijaya, Adrianus Gupta; Telussa, Arley Sadra (Universitas Nusa Cendana, 2021)
Giant bladder stone is a rare case of urinary tract stones. This case usually occurs because of delayed diagnosis due to limited medical facility. Cases Three cases of giant bladder stone were reported in Dilumil Public Health Center, East Nusa Tenggara. All patients are male. The first patient is 40 years old with a 9 x 8.7 x 6 cm bladder stone and that weighed 425 g. The second patient is 19 years old with a 6 x 5.5 x 5.5cm bladder stone and that weighed 116.5g. The third patient is 18 years old with 4.8 x 3.8 x 3.7cm stone and that weighed 105g. Two of three patient’s main complaint was urinary retention, while other patient complained of dysuria. All cases were treated with open vesicolithotomy. Conclusion Giant bladder stone weighing > 100g is uncommon. Initial careful diagnosis is needed to prevent delays in handling bladder stones in primary health facilities. These patients live in the same area and share the drinking water source. The bladder stone was removed by open vesicolithotomy without any complications.